Research on power quality comprehensive treatment for coal mine - GUO Songmei (Gong-kuang zidonghua, 2016)
For problems of harmonics pollution and voltage fluctuation existed in power quality of coal mine, a power quality comprehensive treatment method based on SVG for coal mine was proposed. The method uses orthogonal transformations theory to realize direct control of active and reactive current, can improve precision of dynamic reactive power compensation, and can suppress influence of grid frequency fluctuation. The simulation results show that the proposed comprehensive treatment method can suppress harmonics caused by nonlinear loads, which improves the comprehensive power quality of coal mine power grid.